Chemotherapy-induced peripheral neuropathy in a dish: dorsal root ganglion cells treated in vitro with paclitaxel show biochemical and physiological responses parallel to that seen in vivo. Issue 1 (January 2021) - Li, Yan; Marri, Tejaswi; North, Robert Y.; Rhodes, Haley R.; Uhelski, Megan L.; Tatsui, Claudio E.; Rhines, Laurence D.; Rao, Ganesh; Corrales, German; Abercrombie, Taylor J.; Johansson, Caj A.; Dougherty, Patrick M.
Abstract : Abstract: The mechanisms underlying chemotherapy-induced peripheral neuropathy have yet to be fully elucidated, but primary afferent neurons have emerged as an especially vulnerable initiating pathophysiological target. An important recent study has also shown that the initial toxicity produced by paclitaxel in patients was highly predictive of long-term outcome. In this study, we therefore focused on defining the mechanisms of acute toxicity produced by paclitaxel treatment on primary sensory neurons under in vitro conditions. In primary rat dorsal root ganglion (DRG) culture with paclitaxel, an increase of pERK and pp38 was observed at 2 hours, and this was accompanied by an increase in expression and release of C-C chemokine ligand 2 (CCL2). There was no change in pJNK. The increase in pERK was sustained at 48 hours of exposure when the expression of TLR4, MyD88, and IL-6 was also increased. IL-6 and CCL2 were colocalized to TLR4-positive cells, and all these responses were prevented by coincubation with a TLR4 antagonist (LPS-RS). Whole-cell patch-clamp recordings revealed that DRG neurons developed spontaneous depolarizing fluctuations (DSFs) in membrane potential and hyperexcitability to current injection but no ectopic action potential activity at 24 and 48 hours of paclitaxel incubation. However, CCL2 applied to cultured neurons not only induced DSFs but also evoked action potentials. Evidence of oxidative stress and mitotoxicity was observed at 48 hours of exposure. These results closely parallel the responses measured in the DRG with paclitaxel exposure in vivo and so indicate that acute toxicity of paclitaxel on the DRG can be modelled using an in vitro approach. Abstract : This work reports the results of in vitro studies of dorsal root ganglion neurons after exposure to the chemotherapeutic paclitaxel. The results show that many of the same biochemical and physiologic responses seen using whole animal models are reproduced in this reduced system.